Ocrelizumab in treatment of primary-progressive multiple sclerosis: systematic review - D. L. Klabukova; M. E. Holownia-Voloskova; M. V. Davydovskaya; T. N. Ermolaeva; E. M. Olyushina; K. I. Polyakova; A. G. Fisun; M. G. Grinin; K. A. Kokushkin (Качественная клиническая практика, 2018)
Aim. To analyze the efficacy, safety and pharmacoeconomic indicators of ocrelizumab in adult patients with primary progressive multiple sclerosis (PPMS). Methods. An information search was conducted in the databases Embase, PubMed, Cochrane and eLibrary.ru. The levels of evidence were determined in the studies. Results. Therapy with ocrelizumab compared with placebo characterized by a decrease in the rate of progression of the disease. Treatment with ocrelizumab was associated with a significant slowdown in progression compared to other drugs: rituximab, fingolimod, myelin basic protein peptide 82–98, intravenous immunoglobulin; plasmapheresis / plasma metabolism, corticosteroids, general irradiation of lymphoid tissue, and other most common adverse events: infusion reactions, nasopharyngitis, upper tract respiratory and urinary tract infections, headaches. Life years and quality-adjusted life years for patients receiving ocrelizumab were 16.11 and 3.33, compared with 15.61 and 2.75 for patients receiving better supportive care, respectively. The annual average potential impact on the budget for 1 patient with PPMS in the treatment of ocrelizumab for 5 years ranged from $ 18,300 to 44 200. Conclusions. Ocrelizumab is the only drug that has proven its clinical efficacy in the previously non-curable type of multiple sclerosis, PPC, with risk profile acceptable with respect to clinical benefits.